Of mice, cattle, and humans: the immunology and treatment of river blindness. - Judith E Allen; Ohene Adjei; Odile Bain; Achim Hoerauf; Wolfgang H Hoffmann; Benjamin L Makepeace; Hartwig Schulz-Key; Vincent N Tanya; Alexander J Trees; Samuel Wanji; David W Taylor (Public Library of Science (PLoS), 2008)
River blindness is a seriously debilitating disease caused by the filarial parasite Onchocerca volvulus, which infects millions in Africa as well as in South and Central America. Research has been hampered by a lack of good animal models, as the parasite can only develop fully in humans and some primates. This review highlights the development of two animal model systems that have allowed significant advances in recent years and hold promise for the future. Experimental findings with Litomosoides sigmodontis in mice and Onchocerca ochengi in cattle are placed in the context of how these models can advance our ability to control the human disease.